Endoscope-controlled Access to Thalamic Tumors using Tubular Brain Retractor: An Alternative Approach to Microscopic Excision - Sihag, Rakesh; Bajaj, Jitin; Yadav, Yad Ram; Ratre, Shailendra; Hedaoo, Ketan; Kumar, Ambuj; Sinha, Mallika; Parihar, Vijay; Swamy, M. Narayan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Surgery for thalamic lesions has been considered challenging due to their deep-seated location. Endoscopic excision of deep-seated brain tumors using tubular retractor has been shown to be safe and effective in prior studies; however, there are limited reports regarding its use for thalamic tumors. We present our experience of endoscope-controlled resection of thalamic tumors using a tubular retractor.Material and Methods This was a prospective observational case series done at a tertiary center specialized for endoscopic neurosurgery during the period from 2010 to 2019. Surgeries were performed under the endoscopic control using a silicon tubular retractor. Lesions were approached transcortically or trans-sulcally. Data were collected for the extent of resection, amount of blood loss, operative time, need for conversion to microscopy, and complications.Results Twenty-one patients of thalamic masses of 14- to 60-year age underwent the surgeries. Pathologies ranged from grade I to IV gliomas. Gross total and near-total resection could be done in 42.85% of cases for each group. The average blood loss and operative time were164.04 ± 83.63 mL and 157.14 ± 28.70 minutes, respectively. Complications included a small brain contusion, two transient hemipareses, and one transient speech deficit.Conclusion Endoscopic excision of thalamic tumors using a tubular retractor was found to be a safe and effective alternative to microscopic resection.
Keywords: endoscopic surgical procedure; endoscopy; glioma; thalamic disease